A wireless sensor network for vibration measurement - Kaplan, Shaun (Department of Electrical Engineering, 2015)
Wireless sensor networks (sensornets) enable distributed sensing, opening up sensing possibilities not previously available. One application of sensornets is online, non-intrusive power transformer monitoring.